2016
DOI: 10.1242/jeb.124446
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of elastic tissues to the mechanics and energetics of muscle function during movement

Abstract: Muscle force production occurs within an environment of tissues that exhibit spring-like behavior, and this elasticity is a critical determinant of muscle performance during locomotion. Muscle force and power output both depend on the speed of contraction, as described by the isotonic force-velocity curve. By influencing the speed of contractile elements, elastic structures can have a profound effect on muscle force, power and work. In very rapid movements, elastic mechanisms can amplify muscle power by storin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
115
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 78 publications
(95 reference statements)
1
115
2
1
Order By: Relevance
“…LPM stiffness increased significantly during stretching and contraction, and this must be related to underlying biological events such as the elastic properties of actomyosin cross‐bridges, hyperemia and edema, and changes in the scaffold of the extracellular matrix (Sarelius et al, ; Roberts, ). Previous studies using SWE and MRE reported positive linear relationships between muscle stiffness and both active and passive muscle forces (Nordez and Hug, ; Hug et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LPM stiffness increased significantly during stretching and contraction, and this must be related to underlying biological events such as the elastic properties of actomyosin cross‐bridges, hyperemia and edema, and changes in the scaffold of the extracellular matrix (Sarelius et al, ; Roberts, ). Previous studies using SWE and MRE reported positive linear relationships between muscle stiffness and both active and passive muscle forces (Nordez and Hug, ; Hug et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…36,37 We found that myosin isoforms 2, 7, and 13 were reduced at either the protein or gene expression level in strabismic muscles, along with several filament- and contraction-related proteins that included troponins, tropomyosins, and titin (Table 1). Titin confers passive elasticity to muscles 4043 ; accordingly, its downregulation may impact and compromise EOM stiffness. Analysis of mutant tropomyosins (causing nemaline myopathy) revealed reduced isometric force when measured in muscles of less than optimal length.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle stretch and contraction elastic elements are major determinants of muscle function and efficient locomotion [4,5]. The measurement of these parameters has largely been explored using myotonometry but this has not been shown to have acceptable accuracy and is limited to superficial muscles only [6,7].…”
Section: Introductionmentioning
confidence: 99%